PENDIDIKAN KARAKTER ANAK MELALUI SIMULASI PENDIDIKAN EDUKASI PADA SISWA SDN SEGARJAYA - Haniyah Salfa Fauziah; Andi Sopandi; Dila Novita (An-Nizam, 2022)
The importance of character education to be applied from an early age needs to be taught since entering school. The implementation method used in this program is education, namely providing knowledge and understanding to students and training, namely role play activities carried out from educational materials based on Pancasila, culture, and religion so that students can imitate and apply them in everyday life. Based on the results of community service activities that have been carried out, it can be seen that the 5th grade students of SDN Segarjaya are able to carry out character education activities well through Pancasila such as not cheating in class and helping friends who need help. Students are also able to apply culture-based character education well, this can be seen from students who say excuse me to the bathroom to the teacher who is teaching during class hours. However, students still have difficulty in carrying out religion-based character education because of the lack of knowledge and understanding of Arabic vocabulary that students have about Arabic sentences.